Chitosan oligosaccharides: A novel and efficient water soluble binder for lithium zinc titanate anode in lithium-ion batteries. (1st January 2015) - Tang, Haoqing; Weng, Qiang; Tang, Zhiyuan
Highlights: Physical properties of chitosan oligosaccharides binder are researched. Electrodes with COS and PVDF binder systems are fabricated to compare physical and electrochemical properties. Li2 ZnTi3 O8 electrode with COS binder system shows improved electrochemical performance. Abstract: Chitosan oligosaccharides (COS) as a new, environmentally and water-based organic compound, is firstly applied as the electrode binder for Li2 ZnTi3 O8 electrode in lithium-ion batteries. Compared with conventional polyvinylidene fluoride (PVDF) binder, the COS binder is used for Li2 ZnTi3 O8 electrode significantly improves the electrochemical performances in terms of the first Columbic efficiency, cycling behavior, rate capability and long life cycle. At 0.1 A g −1, the initial discharge capacity of 215.6 mAh g −1 can be obtained for Li2 ZnTi3 O8 with COS binder system and the Columbic efficiency is as high as 93.6%, which are apparently better than PVDF binder system. Moreover, 66.1 mAh g −1 can be remained after 1000 cycles and the retention is 33.6% for COS binder system, while the PVDF binder system has only 37.9 mAh g −1 (22.8%). In addition, the cycling stability of Li2 ZnTi3 O8 electrode has been improved after using COS as binder. The elevated electrochemical performances of Li2 ZnTi3 O8 electrode with COS binder system can be ascribed to the characters of COS binder, which not only provide numerous hydroxyl groups formed strong hydrogen binds with both active materials and copper current collector, but also suppress swelling of electrode with electrolyte solution.